Why parents matter: exploring the impact of a hegemonic concern with the timetable for the child. Issue 2 (17th February 2014) - Holt, Kim; Kelly, Nancy
Abstract: In a climate of austerity, timescales and targets, this paper probes whether parents matter sufficiently within the current child protection system in England. Evidence suggests that achieving partnership working in the context of child protection has become increasingly illusive, particularly when parents are notified that the local authority is considering compulsory intervention to remove their children under the Children Act 1989. Recent changes to legislation, policy and practice ushered in with the aim of achieving earlier decisions within the time frame for the child are laudable, but there are consequences for both children and their parents. The aspirations of the Public Law Outline (2008) are well rehearsed, but the changes being introduced with the recent reform of the family justice system, alongside particular constructions of parenting, may be failing to recognize the potential of many parents, if offered appropriate support, to care safely for their children.